Intermittent Hypoxia Increases the Severity of Bleomycin-Induced Lung Injury in Mice. (14th March 2018) - Gille, Thomas; Didier, Morgane; Rotenberg, Cécile; Delbrel, Eva; Marchant, Dominique; Sutton, Angela; Dard, Nicolas; Haine, Liasmine; Voituron, Nicolas; Bernaudin, Jean-François; Valeyre, Dominique; Nunes, Hilario; et al.
Abstract : Background . Severe obstructive sleep apnea (OSA) with chronic intermittent hypoxia (IH) is common in idiopathic pulmonary fibrosis (IPF). Here, we evaluated the impact of IH on bleomycin- (BLM-) induced pulmonary fibrosis in mice. Methods . C57BL/6J mice received intratracheal BLM or saline and were exposed to IH (40 cycles/hour; FiO2 nadir: 6%; 8 hours/day) or intermittent air (IA). In the four experimental groups, we evaluated (i) survival; (ii) alveolar inflammation, pulmonary edema, lung oxidative stress, and antioxidant enzymes; (iii) lung cell apoptosis; and (iv) pulmonary fibrosis. Results . Survival at day 21 was lower in the BLM-IH group (p < 0.05 ). Pulmonary fibrosis was more severe at day 21 in BLM-IH mice, as assessed by lung collagen content (p = 0.02 ) and histology. At day 4, BLM-IH mice developed a more severe neutrophilic alveolitis, (p < 0.001 ). Lung oxidative stress was observed, and superoxide dismutase and glutathione peroxidase expression was decreased in BLM-IH mice (p < 0.05 versus BLM-IA group). At day 8, pulmonary edema was observed and lung cell apoptosis was increased in the BLM-IH group. Conclusion . These results show that exposure to chronic IH increases mortality, lung inflammation, and lung fibrosis in BLM-treated mice. This study raises the question of the worsening impact of severe OSA in IPF patients.